CULTURAL DETERMINANTS OF HEALTH AND HEALTHY AGING FOR OLDER ADULTS WITH LIMITED-ENGLISH PROFICIENCY. (11th November 2018) - Park, L; Jacobs, E
Abstract: The absence of "culture" when discussing social determinants of health has created barriers to healthy aging for older adults with limited-English proficiency (LEP). Cultural determinants of health are critical to the study of aging and health, given that today's unprecedented number of older adults (65 years plus) are also the most diverse than any time in our history. Our rapidly aging population includes a growing LEP immigrant and refugee sub-population who experience significant health disparities compared to English-proficient older adults. This paper is a secondary analysis from a parent study that explored barriers and facilitators to preventive cancer screenings for Hmong and Spanish-speaking LEP patients in a large healthcare system in the Midwest (N=20). Three themes emerged regarding LEP older adults' health behavior: (1) adherence to cultural beliefs about health and illness, (2) differential attitudes between traditional healing practices and western medicine, and (3) a general distrust of western healthcare. Results suggest language barriers led to stronger adherence to their cultural attitudes about health in part because of their limitation to understand American culture. The LEP patient present unique challenges, especially since a language barrier is not an isolated situation. It is critical to understand how the combination effect of language and culture create cross-cultural barriers on health outcomes because their perspective on health and illness does not align with the US healthcare system perspective. Understanding the cultural determinants of health is an important factor to consider as this aging LEP population are at greater risk for age-related health complications.